Antiseptic Activity of Combination Lotion of Herbal Extracts of Gotu Kola (Centella Asiatica (L). Urban) and Aloe Vera Against Psedomonas Aeruginosa Bacteria - Delladari Mayefis; Rury Trisa Utami; Mulyani Ardian Ningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
To test the antibacterial activity of antiseptic gel, a combination of gotu kola herb extract and aloe vera extract against pseudomonas aeruginosa bacteria. Experimentally using the well diffusion method with a combined concentration of gotu kola and aloe vera herbal extracts of 5%:5% (F IV), 7.5%:2.5% (F V), 7.5%:2.5% (F VI), with positive control using antic antiseptic. The antibacterial activity with the antiseptic combination of gotu kola and aloe vera herbal extracts against pseudomonas aeruginosa bacteria has a medium category inhibitory power of 18.06 mm. The data obtained was tested for normality using the Shapiro Wilk test followed by the One Way Anova test. Based on statistical tests using ANOVA, it shows that there is a significant difference between the average percentage values between groups (sig ≤ 0.05). The single lotion activity and antibacterial combination of gotu kola and aloe vera herbal extracts can inhibit the growth of pseudomonas aeruginosa bacteria